Using Employment Data From a Medical University to Examine the Current Occupation Situation of Master's Graduates in Public Health and Preventive Medicine in China - Huangyuan Li; Fuli Zheng; Jie Zhang; Zhenkun Guo; Hua Yang; Caixia Ren; Wenchang Zhang; Siying Wu (Frontiers Media S.A., 2020)
Aims: The purposes of this study are (1) to understand the current employment situation of master's graduates in Public Health and Preventive Medicine (PHPM) and (2) to provide evidence for career guidance and training of competent PHPM personnel.Methods: The master's graduates of the School of Public Health from the years 2014-2018 who majored in PHPM were chosen as research subjects. Questionnaires were distributed, and completed questionnaires were collected. The employment situation and characteristics of these graduates were analyzed based on the questionnaire data.Results: The employment rate of these graduates was 95.45%. They were employed mainly in hospitals, followed by colleges and centers for disease control and prevention. The initial salaries were low. Graduates whose jobs barely or not at all matched their areas of specialization were 23.64 or 6.36%, respectively. Nevertheless, the percentage of students who had remained with their jobs since graduation was 82.73%. A total of 40% of the graduates were neutral about or dissatisfied with their jobs. Furthermore, 29% of them claimed that they were undervalued by their employers. Last, but not least, graduates were encouraged to gain experience in creativity, organizational or management skills, social networking experience, and interpersonal and professional skills.Conclusion: Overall, the employment status of master's graduates in PHPM is good. Problems such as low initial salaries, jobs not matching graduates' areas of specialization, and feelings of being undervalued by employers were observed. It is necessary to improve employment outcomes by revising training models, formulating employment policies, and implementing training efforts.